Shared Food, Meals and Drinks: 10 Arguments Suggesting an Oral Transmission Route of SARS-CoV-2 - Wendling, Jean-Michel; Saulnier, Aure; Sabatier, Jean-Marc (Infectious Disorders - Drug Targets, 2022)
Numerous observational, epidemiologic data have suggested that the risk of COVID19 is related to shared meals or drinks. The presence of ACE2 receptors in the gastrointestinal tract supports this hypothesis. Furthermore, several patients experience gastrointestinal symptoms without any respiratory disease. The SARS-CoV-2 found on food and packaging in China and the epidemic resurgence attributed to foods are also strong indications of an oral transmission route. Unprecedented biopersistence on skin, food, and beverages supports this theory. Finally, animal models reproducing the disease by oral inoculation are additional arguments in favor of an oro-digestive route of infection.
Keywords: COVID-19